GRAIN PROTEIN FRACTIONS OF INDIAN RICE VARIETIES - K.UMADEVI, G.NIHARIKA, V. VIJAYALAKSHMI, D. SANJEEV M. SHESHU MADAV and (The Journal of Research, PJTSAU, 2019)
Rice is one of the world’s cereal staple and an important crop in Asia. Rice protein is a second dominant principal nutrient and the sole protein source for underprivileged people. Based on Osborn classification of solubility, protein fractions are classified into glutelins, albumins, globulins and prolamins and their solubility in alkali, water, salt and alcohol respectively. The present investigation is focused on assessing total protein and protein fractions. The protein fractions and total protein were isolated by specific extraction buffers from rice flour and quantified by Lowry method. The selected varieties for this study showed the rangeof total protein albumin, globulin, prolamin and glutelin from 4.95% (Vibhava) to 6.52% (BPT5204) and on par with Ravi (6.09%); 0.03% (Rasi) to 0.54% (Vibhava); 0.02% (Sampada) to 0.07% (Vibhava); 0.28% (Sampada) to 0.82% (Rasi); and 0.16% (Rasi) to 0.61% (BPT5204) respectively. Among varieties total protein, albumin and globulin were statistically significant and prolamin and glutelin are found to be non-significant at p